A FeP-doped polytriazine carbon material and its preparation method and application in selective capacitive deionization electrode

Through FeP-doped polytriazine carbon material, FeP particles are generated by in-situ polymerization and calcination, the problem of insufficient adsorption performance of existing materials on Cu2+ is solved, and the efficient and low-consumption Cu2+ separation effect is achieved.

CN116395650BActive Publication Date: 2025-03-18ANHUI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310595263.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-03-18
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

The selective adsorption performance of existing polytriazine carbon materials to Cu2+ is poor, and the metal doping amount is difficult to control.

Method used

Using FeP-doped polytriazine carbon material, P elements are polymerized in situ through the reaction of 2,6-diaminopyridine, formaldehyde and phytic acid, and mixed with ferric nitrate to generate aggregated FeP particles through the calcination process, and their content is controlled to improve the selective adsorption performance of Cu2+.

Benefits of technology

It achieves excellent selective adsorption performance for Cu2+, and the doping amount is easy to control, and the Cu2+ adsorption capacity of the material is improved, which is suitable for low-consumption and efficient separation of Cu2+ in wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395650B_ABST
    Figure CN116395650B_ABST
Patent Text Reader

Abstract

The invention discloses a FeP-doped polytriazine carbon material and a preparation method thereof and an application in a selective capacitive deionization electrode. The preparation method of the FeP-doped polytriazine carbon material comprises the following steps: mixing and dissolving water and 2,6-diaminopyridine, adding formaldehyde, stirring at room temperature until the solution turns gray, adding phytic acid and continuing to stir the reaction, and after the reaction is completed, solid-liquid separation and drying are performed to obtain an intermediate sample; the intermediate sample and ferric nitrate are stirred in methanol, dried, and calcined under nitrogen protection, and the obtained product is purified and dried to obtain the FeP-doped polytriazine carbon material. The preparation method of the carbon material of the invention is simple, and the electrode material prepared by the same can separate Cu with a high content in wastewater with low consumption and high efficiency. 2+ .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to an FeP-doped polytriazine carbon material and a preparation method thereof, and application thereof in a selective capacitive deionization electrode. Background Art

[0002] Copper-containing wastewater is wastewater generated by industries such as metallurgy and electronics, mainly including printed circuit board etching wastewater, electroplating wastewater, etc. The discharge of heavy metal copper ions is extremely harmful to water bodies and soil. Copper is one of the essential trace elements for the human body, but if the copper content in the human body exceeds the standard, it will burden human organs, especially the liver and gallbladder. The direct discharge of copper-containing wastewater not only pollutes the environment, but also wastes resources. Therefore, it is necessary to treat copper-containing wastewater, recover copper through technical means, and discharge it after the water quality meets the standard. Common methods include concentration, extraction, adsorption and ultrasonic degradation. Such traditional separation and purification methods have high energy consumption, low efficiency and low selectivity.

[0003] The Chinese patent application document with publication number CN115285950A discloses a method for preparing a polytriazine carbon material, comprising the following steps: adding sulfuric acid solution to water and stirring evenly, then adding 2,6-diaminopyridine and transition metal Lewis acid and stirring until dissolved, then adding formaldehyde, stirring at room temperature and centrifuging and concentrating, transferring to an autoclave for reaction, heating and continuing the reaction after the reaction is completed, centrifuging, drying, and obtaining a semi-finished product; heating and calcining the semi-finished product under nitrogen protection, washing with hydrochloric acid solution, then extracting with Soxhlet in water, drying, and obtaining a polytriazine carbon material. It can be used to prepare CDI electrode materials, and then treat contaminated water containing heavy metal ions to achieve selective adsorption-desorption of special heavy metal ions. Compared with traditional electrode materials, nitrogen-doped carbon, the CDI electrode materials prepared therefrom are green, efficient, low-carbon, and sustainable, and have played an important role in responding to major challenges such as resource shortages, energy crises, and environmental deterioration; however, the metal doped therein is at the single-atom level, small in size, and very low in content (atomic content is less than 0.5%). During the synthesis of the material, the metal content is difficult to control. At the same time, the CDI electrode material prepared by the method has a certain influence on the Mn 2+ It has obvious selective adsorption and large adsorption capacity, but its adsorption to Cu 2+ The selective adsorption performance is poor. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a FeP-doped polytriazine carbon material and a preparation method thereof, and a capacitor deionization electrode made of the same for Cu 2+ It has excellent selective adsorption performance.

[0005] The present invention solves the above technical problems through the following technical means:

[0006] A method for preparing a FeP-doped polytriazine carbon material comprises the following steps:

[0007] S1. Mix and dissolve water and 2,6-diaminopyridine, add formaldehyde, stir at room temperature until the solution turns gray, add phytic acid and continue stirring to react, separate the solid and liquid after the reaction is completed, and dry to obtain an intermediate sample;

[0008] S2. Stir the intermediate sample and ferric nitrate in methanol, dry and then calcine under nitrogen protection, purify and dry the obtained product to obtain the FeP-doped polytriazine carbon material.

[0009] Preferably, in S1, the formaldehyde is added in the form of a 30% formalin solution by mass; the mass volume ratio of the 2,6-diaminopyridine, the 30% formalin solution, and the phytic acid is 300 mg: 450 μL: 1-2 ml.

[0010] Preferably, in S1, the stirring reaction time after adding phytic acid is continued for 20-30 hours.

[0011] Preferably, in S1, the stirring reaction time after adding phytic acid is continued for 24 hours.

[0012] Preferably, in S2, the mass ratio of the intermediate sample to ferric nitrate is 6-20:1.

[0013] Preferably, in S2, the mass ratio of the intermediate sample to ferric nitrate is 12-15:1.

[0014] Preferably, in S2, the mass ratio of the intermediate sample to ferric nitrate is 15:1.

[0015] Preferably, in S2, the stirring time is 20-30 hours.

[0016] Preferably, in S2, the stirring time is 24 hours.

[0017] Preferably, in S2, the calcination includes a first stage calcination and a second stage calcination; the temperature of the first stage calcination is 550-650°C, the time is 4-6h, and the heating rate is 3-6°C / min; the temperature of the second stage calcination is 900-950°C, the time is 45-90min, and the heating rate is 3-6°C / min.

[0018] Preferably, in S2, the calcination includes a first stage calcination and a second stage calcination; the temperature of the first stage calcination is 600°C, the time is 5h, and the heating rate is 5°C / min; the temperature of the second stage calcination is 920°C, the time is 60min, and the heating rate is 5°C / min.

[0019] The present invention also provides a FeP-doped polytriazine carbon material, which is prepared by adopting the preparation method of the FeP-doped polytriazine carbon material.

[0020] The present invention also proposes an application of the FeP-doped polytriazine carbon material in preparing a capacitive deionization electrode for selectively adsorbing heavy metal ions.

[0021] Preferably, the heavy metal ions are copper ions.

[0022] The present invention also provides a capacitor deionization electrode for selectively adsorbing heavy metal ions, which is prepared by using the FeP-doped polytriazine carbon material as a raw material.

[0023] The present invention also proposes a method for preparing the capacitive deionization electrode for selectively adsorbing heavy metal ions, comprising the following steps: grinding FeP-doped polytriazine carbon material, acetylene black, PVDF, and NMP into a uniform slurry, then coating it on graphite paper, standing it at room temperature, and assembling it after drying to obtain the capacitive deionization electrode for selectively adsorbing heavy metal ions.

[0024] The invention has the advantages that: in the preparation method of the FeP-doped polytriazine carbon material, 2,6-diaminopyridine, formaldehyde and phytic acid are first used as raw materials to react and in-situ polymerize P elements, and then mixed with ferric nitrate, and the in-situ polymerized P elements and ferric nitrate generate aggregated FeP particles in-situ during the calcination process, and the size of the FeP particles is large; the final FeP content can be controlled by the amount of ferric nitrate added during the calcination process, and the doping amount is easy to control; the material finally obtained is a FeP-doped nitrogen-containing carbon material; the electrode material prepared with the material can separate Cu with a high content in wastewater with low consumption and high efficiency. 2+ . BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The maximum salt adsorption capacity of various metal chloride salts by the capacitive deionization electrode made of the material prepared in Example 1 of the present invention;

[0026] Figure 2 The adsorption-desorption curves of various metal ions of the capacitive deionization electrode made of the material prepared in Example 1 of the present invention;

[0027] Figure 3 XRD images corresponding to the FeP-doped polytriazine carbon materials prepared in Examples 1-2 and 4 of the present invention;

[0028] Figure 4 A transmission electron microscope (TEM) image of the lattice fringes corresponding to the FeP-doped polytriazine carbon material prepared in Example 1 of the present invention;

[0029] Figure 5The adsorption-desorption curves of the capacitive deionization electrode made of the materials prepared in Example 1 and Comparative Example 1 of the present invention for copper chloride salt;

[0030] Figure 6 The maximum salt adsorption capacity of various metal chloride salts by the capacitive deionization electrodes made of the materials prepared in Examples 1, 2 and 4 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0033] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0034] Example 1

[0035] A preparation method of a FeP-doped polytriazine carbon material comprises the following steps: adding 300 mg of 2,6-diaminopyridine to 600 mL of H2O, stirring and dissolving the mixture, adding 450 μL of a formalin solution with a mass fraction of 30%, stirring the mixture at room temperature until the solution turns gray, adding 1 mL of phytic acid, stirring the mixture at room temperature for 24 hours, centrifuging the mixture, and drying the mixture in a 60°C oven for 24 hours. The dried sample and Fe(NO3)3 are immersed in a methanol solution at a mass ratio of 15:1 and stirred for 24 hours, and then the sample is placed in a 60°C oven for drying. After drying, the sample is placed in a high-temperature tubular furnace and calcined in stages under nitrogen protection, wherein the first stage is heated to 600°C at a heating rate of 5°C / min and calcined for 5 hours, and the second stage is heated to 920°C at a heating rate of 5°C / min and calcined for 1 hour, and then the obtained sample is subjected to Soxhlet extraction in methanol for 72 hours, and the FeP-doped polytriazine carbon material is obtained after drying.

[0036] Example 2

[0037] A preparation method of a FeP-doped polytriazine carbon material comprises the following steps: taking 600 mL of H2O and adding 300 mg of 2,6-diaminopyridine, stirring and dissolving the mixture, adding 450 μL of a formalin solution with a mass fraction of 30%, stirring the mixture at room temperature until the solution turns gray, adding 2 mL of phytic acid, stirring the mixture at room temperature for 20 hours, centrifuging the mixture, and drying the mixture in a 60°C oven for 24 hours. The dried sample and Fe(NO3)3 are immersed in a methanol solution at a mass ratio of 6:1 and stirred for 24 hours, and then the sample is placed in a 60°C oven for drying. After drying, the sample is placed in a high-temperature tubular furnace and calcined in stages under nitrogen protection, wherein the first stage is heated to 550°C at a heating rate of 3°C / min and calcined for 6 hours, and the second stage is heated to 950°C at a heating rate of 3°C / min and calcined for 45 minutes, and then the obtained sample is subjected to Soxhlet extraction in methanol for 72 hours, and the FeP-doped polytriazine carbon material is obtained after drying.

[0038] Example 3

[0039] A preparation method of a FeP-doped polytriazine carbon material comprises the following steps: adding 300 mg of 2,6-diaminopyridine to 600 mL of H2O, stirring and dissolving the mixture, adding 450 μL of a formalin solution with a mass fraction of 30%, stirring the mixture at room temperature until the solution turns gray, adding 1.5 mL of phytic acid, stirring the mixture at room temperature for 30 hours, centrifuging the mixture, and drying the mixture in a 60°C oven for 24 hours. The dried sample and Fe(NO3)3 are immersed in a methanol solution at a mass ratio of 12:1 and stirred for 20 hours, and then the sample is placed in a 60°C oven for drying. After drying, the sample is placed in a high-temperature tubular furnace and calcined in stages under nitrogen protection, wherein the first stage is heated to 600°C at a heating rate of 6°C / min and calcined for 5 hours, and the second stage is heated to 920°C at a heating rate of 6°C / min and calcined for 1 hour, and then the obtained sample is subjected to Soxhlet extraction in methanol for 72 hours, and the FeP-doped polytriazine carbon material is obtained after drying.

[0040] Example 4

[0041] A preparation method of a FeP-doped polytriazine carbon material comprises the following steps: adding 300 mg of 2,6-diaminopyridine to 600 mL of H2O, stirring and dissolving the mixture, adding 450 μL of a 30% formalin solution, stirring the mixture at room temperature until the solution turns gray, adding 1 mL of phytic acid, stirring the mixture at room temperature for 24 hours, centrifuging the mixture, and drying the mixture in a 60°C oven for 30 hours. Soaking the dried sample and Fe(NO3)3 in a methanol solution at a mass ratio of 20:1 and stirring the mixture for 30 hours, and then drying the sample in a 60°C oven. After drying, the sample is placed in a high-temperature tubular furnace and calcined in stages under nitrogen protection. The first stage is heated to 650°C at a heating rate of 5°C / min and calcined for 4 hours, and the second stage is heated to 900°C at a heating rate of 5°C / min and calcined for 90 minutes. The obtained sample is then subjected to Soxhlet extraction in methanol for 72 hours, and the FeP-doped polytriazine carbon material is obtained after drying.

[0042] Figure 3 XRD images corresponding to the FeP-doped polytriazine carbon materials prepared in Examples 1-2 and 4 of the present invention, wherein the curve represented by 15:1 represents Example 1, the curve represented by 6:1 represents Example 2, and the curve represented by 20:1 represents Example 4; Figure 3 It can be seen that, corresponding to the PDF card, it is confirmed that the sample contains FeP, and as the content of ferric nitrate increases, the FeP content in the final sample also increases.

[0043] Figure 4 TEM image of the lattice fringes corresponding to the FeP-doped polytriazine carbon material prepared in Example 1 of the present invention; Figure 4 It can be seen that the lattice fringe analysis further proves that the lattice phase in the sample is FeP.

[0044] Comparative Example 1

[0045] A preparation method of a polytriazine carbon material doped with P comprises the following steps: adding 300 mg of 2,6-diaminopyridine to 600 mL of H2O, stirring and dissolving the mixture, adding 450 μL of a formalin solution having a mass fraction of 30%, stirring the mixture at room temperature until the solution turns gray, adding 1 mL of phytic acid, stirring the mixture at room temperature for 24 hours, centrifuging the mixture, and drying the mixture in a 60°C oven for 30 hours. After drying, the mixture is placed in a high-temperature tubular furnace and calcined in stages under nitrogen protection, wherein the first stage is heated to 650°C at a heating rate of 5°C / min and calcined for 4 hours, and the second stage is heated to 900°C at a heating rate of 5°C / min and calcined for 90 minutes, and then the obtained sample is subjected to Soxhlet extraction in methanol for 72 hours, and the polytriazine carbon material doped with P is obtained after drying.

[0046] Example 5

[0047] Take 60 mg of the material samples prepared in Examples 1-2, Example 4 and Comparative Example 1 respectively, place the prepared material samples, acetylene black and PVDF in a mortar at a mass ratio of 8:1:1, add 750 μL of NMP, grind into a uniform slurry, and then evenly apply it on two 4 cm×4 cm graphite papers, let it stand at room temperature for 2 h, transfer it to an oven at 60°C for drying for 8 h, and assemble the CDI instrument.

[0048] The electrosorption performance of CDI electrode materials was tested at a flow rate of 10 mL / min, at room temperature, with an adsorption voltage of 1.2 V and an adsorption and desorption time of 3600 s. The circulating solution was a 500 mg / L aqueous solution of various heavy metal ions (with NaCl as a reference). The test results are shown in Figure 2. Figure 1-2 , Figure 5-6 As shown, Figure 5 In the example, FeP doping represents Example 1, and P doping represents Comparative Example 1. Figure 6 6:1 represents Example 2, 15:1 represents Example 1, and 20:1 represents Example 4; Figure 1-2 It can be seen that the prepared electrode material has a relatively obvious selective adsorption of metal cations. Compared with other metal cations, the electrode has a relatively high selectivity for Cu 2+ It has excellent adsorption performance; Figure 5-6 It can be seen that the adsorption capacity of FeP-doped electrode materials is better than that of P-doped electrode materials ( Figure 5 ), and the adsorption performance test of electrode materials with different FeP contents showed that the performance of the sample with a ratio of 15:1 was the best ( Figure 6 ).

[0049] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a FeP-doped polytriazine carbon material, characterized in that: The following steps are involved: S1. Mix and dissolve water and 2,6-diaminopyridine, add formaldehyde, stir at room temperature until the solution turns gray, add phytic acid and continue stirring to react, separate the solid and liquid after the reaction is completed, and dry to obtain an intermediate sample; S2. Stir the intermediate sample and ferric nitrate in methanol, dry and then calcine under nitrogen protection, purify and dry the obtained product to obtain the FeP-doped polytriazine carbon material; wherein the mass ratio of the intermediate sample to ferric nitrate is 15:

1.

2. The method for preparing the FeP-doped polytriazine carbon material according to claim 1, characterized in that: In S1, the formaldehyde is added in the form of a 30% formalin solution by mass; the mass volume ratio of the 2,6-diaminopyridine, the 30% formalin solution, and the phytic acid is 300 mg: 450 μL: 1-2 ml.

3. The method for preparing the FeP-doped polytriazine carbon material according to claim 1, characterized in that: In S1, the stirring reaction time after adding phytic acid is continued for 20-30 hours.

4. The method for preparing the FeP-doped polytriazine carbon material according to claim 1, characterized in that: In S2, the stirring time is 20-30 hours.

5. The method for preparing the FeP-doped polytriazine carbon material according to any one of claims 1 to 4, characterized in that: In S2, the calcination includes a first stage calcination and a second stage calcination; the temperature of the first stage calcination is 550-650°C, the time is 4-6h, and the heating rate is 3-6°C / min; the temperature of the second stage calcination is 900-950°C, the time is 45-90min, and the heating rate is 3-6°C / min.

6. A FeP-doped polytriazine carbon material, characterized in that: The polytriazine carbon material doped with FeP is prepared by the preparation method of the polytriazine carbon material doped with FeP as described in any one of claims 1 to 5.

7. Use of the FeP-doped polytriazine carbon material as claimed in claim 6 in preparing a capacitive deionization electrode for selectively adsorbing heavy metal ions.

8. A capacitive deionization electrode for selectively adsorbing heavy metal ions, characterized in that: The method is prepared using the FeP-doped polytriazine carbon material as claimed in claim 6 as raw material.

9. A method for preparing a capacitive deionization electrode for selectively adsorbing heavy metal ions as claimed in claim 8, characterized in that: The method comprises the following steps: grinding FeP-doped polytriazine carbon material, acetylene black, PVDF and NMP into uniform slurry, coating the slurry on graphite paper, standing the slurry at room temperature, and assembling the slurry after drying to obtain the capacitive deionization electrode for selectively adsorbing heavy metal ions.

Citation Information

Patent Citations

  • Polytriazine carbon material as well as preparation method and application thereof

    CN115285950A